Preparation method of polypropylene-based lead shielding gamma-ray composite material with excellent processability

Through melt reaction blending and hot pressing treatment, the problem of poor compatibility between polypropylene and metal particles is solved, and the molding processing performance and γ-ray shielding performance of polypropylene-based lead composite materials are improved, which is suitable for the field of ionizing radiation protection.

CN119144082APending Publication Date: 2024-12-17TECHN PHYSICS INST HEILONGJIANG ACADOF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410820592.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Conventional polypropylene has poor composite compatibility with metal particles, low melt strength and high processing difficulty, which limits its application in the field of high-performance materials.

Method used

The melt reaction blending method is adopted, polypropylene is used as the matrix, polybutadiene nanorubber is the reinforcement, acrylamide is used as the compatibilizer, lead oxide is used as the gamma-ray shielding particles, and is passed through a torque rheometer and a flat vulcanizer Perform hot pressing, control temperature and rotation speed for improved compatibility and melt strength.

Benefits of technology

It has achieved excellent molding and processing performance of polypropylene-based lead composite materials, improved γ-ray shielding performance and thermal stability, and is suitable for the field of ionizing radiation protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144082A_ABST
    Figure CN119144082A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polypropylene-based lead shielding gamma-ray composite material with excellent processability, and belongs to the field of ionizing radiation shielding materials. The technical problems that existing conventional polypropylene and metal particles are poor in compounding compatibility, low in melt strength and high in processing difficulty are solved. The method comprises the following steps: taking polypropylene as a matrix, polybutadiene nano rubber as a reinforcement, acrylamide as a compatilizer and lead oxide as shielding metal particles; the polypropylene-based lead composite material with long-chain branching characteristics, uniform lead oxide particle dispersion, high thermal stability and good gamma-ray shielding performance and processability is prepared through a wet reaction melt blending method. The method is easy to operate, the polypropylene-based lead composite material can have the long-chain branching characteristic, the forming processing performance is improved, lead oxide particles are evenly dispersed, the crystallization temperature is increased, the thermal stability is improved, and the shielding performance is excellent. The prepared composite material is applied to the field of ionizing radiation protection with limited space and maneuverability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ionizing radiation shielding materials, and in particular relates to a method for preparing a polypropylene-based lead-shielding gamma-ray composite material. Background Art

[0002] The use of lightweight polymer materials as a matrix and heavy metal composites has broad application prospects in the field of gamma-ray shielding. Currently, common matrix materials include polyethylene, unsaturated polyester and polypropylene. Among them, polypropylene has good temperature resistance, chemical corrosion resistance, processing performance and recyclability. However, conventional polypropylene has poor compatibility with metal particles, low melt strength and great difficulty in molding and processing, which limits its application in the field of high-performance material processing. Long-chain branched polypropylene is a new type of polypropylene material developed to address the processing performance defects of conventional polypropylene. Long-chain branched polypropylene has a high crystallization temperature and a fast crystallization rate, is suitable for high-temperature demolding, and has strain hardening during melt stretching; the processing temperature range is wide and can be used for thermoforming, extrusion foaming, coating, blow molding and other aspects. However, whether the prepared polypropylene has long-chain branching characteristics is affected by the interaction and compatibility between the blend components. Lead is currently a more effective metal element for shielding γ-rays. The molecular structure of polypropylene and the dispersibility of lead particles will affect whether the polypropylene-based lead composite material forms long-chain branching characteristics, thereby affecting the shielding performance of the polypropylene-based lead composite material. Therefore, it is urgent to develop polymer-based composite materials with excellent molding and processing performance for shielding γ-rays. Summary of the invention

[0003] The invention solves the technical problems of poor composite compatibility between conventional polypropylene and metal particles, low melt strength and great processing difficulty, and further provides a method for preparing a polypropylene-based lead shielding gamma-ray composite material with excellent processing performance.

[0004] The polypropylene-based lead-shielding gamma-ray composite material with excellent processing performance adopts a melt reaction blending method, with polypropylene as a matrix, polybutadiene nano rubber as a reinforcement, acrylamide as a compatibilizer, and lead oxide as gamma-ray shielding particles.

[0005] A method for preparing a polypropylene-based lead shielding gamma-ray composite material with excellent processing performance is specifically carried out in the following steps:

[0006] Putting polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles into a torque rheometer, controlling the speed to be 30 rpm to 90 rpm and the temperature to be 160° C. to 220° C., melt blending for 5 min to 20 min, and then hot pressing on a flat vulcanizer to obtain the polypropylene-based lead shielding γ-ray composite material with excellent processing performance;

[0007] The mass ratio of the polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (1-10): (1-10): (20-80).

[0008] The beneficial effects of the present invention are:

[0009] The invention prepares a polypropylene-based lead-shielded gamma-ray composite material with excellent molding and processing performance by melt-blending polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles through a wet reaction and a one-step process, thereby solving the problems of poor composite compatibility between conventional polypropylene and metal particles, low melt strength and great processing difficulty.

[0010] The invention solves the compatibility problem by adding a compatibilizer acrylamide, because acrylamide molecules contain double bonds, which can undergo grafting reaction with polypropylene and polybutadiene nano rubber when heated, and in addition, a large number of amide groups are contained in the molecules, and hydrogen bonds are formed between the hydrogen and oxygen atoms on these amide groups. In the process of melt blending, the shear force and hydrogen bond action and the pressure provided during the evaporation of water in the polybutadiene nano rubber emulsion during the heating process work together to improve the dispersion of gamma-ray shielding functional particles of lead oxide in the polypropylene matrix, thereby improving the compatibility between different components. Adding the toughening agent polybutadiene nano rubber emulsion improves the strength of the melt, and the polybutadiene particles in the nano rubber emulsion are very small in size, reaching the nano level, and are evenly dispersed in the polypropylene matrix. The contact area between nanoparticles and matrix materials is increased, thereby improving the bonding strength of the interface. At the same time, nano rubber has the effect of toughening rubber and plastic and the increase in the amount of lead oxide added to improve the strength of the polypropylene matrix. After polyacrylamide is grafted with polypropylene and polybutadiene nano rubber, as well as the hydrogen bonds formed between polyacrylamide molecules, the two work together to form a heterogeneous network structure in the polypropylene matrix. The heterogeneous network structure improves the density of the heterogeneous network structure through the regulation of components and processes, promotes the formation of long-chain branching characteristics of polypropylene, improves the melt strength of polypropylene, and solves the problem of low melt strength. Long-chain branching characteristic polypropylene is a new type of polypropylene material developed to address the defects of its processing performance. Long-chain branched polypropylene has a high crystallization temperature and a fast crystallization speed, is suitable for high-temperature demolding, has strain hardening during melt stretching, and has a wide processing temperature range. It can be used for thermoforming, extrusion foaming, coating, blow molding, etc. Long-chain branched polypropylene products have good thermal stability and dimensional stability at high temperatures, high toughness and tensile strength, good environmental effects and easy recycling.

[0011] The method of the present invention is not only simple to operate, but also can make the polypropylene-based lead composite material have long-chain branching characteristics, improved molding and processing performance, uniform dispersion of lead oxide particles, increased crystallization temperature, increased thermal stability, and excellent shielding performance, and can be used in the field of ionizing radiation protection with limited space and mobility.

[0012] The mass ratio of the polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles of the invention is (5-65): (1-10): (1-10): (20-80), so that the polypropylene-based lead composite material has good molding processing performance, crystallization performance, aging performance and gamma-ray shielding performance. The rotation speed of the melt blending is 30 rpm-90 rpm and the temperature is 160 DEG C-220 DEG C. Meanwhile, the lead oxide particles are heated and stirred for 5 min-15 min, so that the lead oxide particles are uniformly dispersed in the polypropylene matrix.

[0013] The polypropylene-based lead-shielding gamma-ray composite material prepared by the invention is suitable for the field of ionizing radiation protection with limited space and mobility. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a flow chart of preparing a polypropylene-based lead shielding γ-ray composite material according to Example 1;

[0015] Figure 2 The complex viscosity-frequency curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Example 1, Example 3 and Example 7;

[0016] Figure 3 The melt flow rate (MFR) diagram of the polypropylene-based lead shielding γ-ray composite material prepared in Example 1 and Example 7;

[0017] Figure 4 This is a scanning electron microscope image of the polypropylene-based lead-shielding γ-ray composite material prepared in Example 1;

[0018] Figure 5 The DSC curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Example 1, Example 5 and Example 6;

[0019] Figure 6 XRD curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Example 1, Example 2 and Example 4;

[0020] Figure 7 Thermogravimetric curves of polypropylene-based lead shielding γ-ray composite materials prepared in Example 1, Example 2 and Example 4;

[0021] Figure 8 The oxidation induction curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Example 1, Example 2 and Example 3;

[0022] Fig. 9 It is a rheological time scanning curve diagram of the polypropylene-based lead shielding γ-ray composite material prepared in Example 1 and Example 7;

[0023] Fig.10 The rheological temperature scanning curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Example 1 and Example 7;

[0024] Fig.11 This is a comparison chart of the linear attenuation coefficients of the polypropylene-based lead-shielding γ-ray composite materials prepared in Example 1 and Example 7;

[0025] Fig.12 This is a comparison chart of the shielding efficiency of the polypropylene-based lead-shielding γ-ray composite materials prepared in Example 1 and Example 7. DETAILED DESCRIPTION

[0026] Specific implementation method 1: This implementation method is a method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance, which is specifically carried out in the following steps:

[0027] Putting polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles into a torque rheometer, controlling the speed to be 30 rpm to 90 rpm and the temperature to be 160° C. to 220° C., melt blending for 5 min to 20 min, and then hot pressing on a flat vulcanizer to obtain the polypropylene-based lead shielding γ-ray composite material with excellent processing performance;

[0028] The mass ratio of the polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (1-10): (1-10): (20-80).

[0029] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles are mixed for 5 to 15 minutes under the condition of controlling the rotation speed to 40 to 90 rpm. The rest is the same as the specific implementation method 1.

[0030] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (2-10): (2-10): (20-80). Other aspects are the same as specific embodiment 1 or 2.

[0031] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (1-8): (1-8): (20-80). Other aspects are the same as specific embodiments 1 to 3.

[0032] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (1-10): (1-10): (20-70). Other aspects are the same as specific embodiments 1 to 4.

[0033] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (10-55): (1-2): (1-2): (40-70). Other aspects are the same as specific embodiments 1 to 5.

[0034] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the heating and stirring are performed for 5 min to 12 min at a rotation speed of 30 rpm to 90 rpm and a temperature of 160° C. to 200° C. The rest is the same as specific embodiments 1 to 6.

[0035] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that heating and stirring are performed for 10 minutes at a rotation speed of 60 rpm and a temperature of 185° C. The rest is the same as specific embodiments 1 to 7.

[0036] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the hot pressing process is controlled at a temperature of 165 to 220° C. and a pressure of 10 to 20 MPa. The rest is the same as specific embodiments 1 to 8.

[0037] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the hot pressing process controls the temperature to be 185-200° C. and the pressure to be 12-19 MPa. The rest is the same as specific embodiments 1 to 9.

[0038] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0039] Embodiment 1:

[0040] The present embodiment provides a method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance, which is specifically carried out in the following steps:

[0041] Putting polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles into a torque rheometer, controlling the speed to be 60 rpm and the temperature to be 185° C., melt blending for 10 minutes, and then hot pressing on a flat vulcanizer to obtain the polypropylene-based lead shielding γ-ray composite material with excellent processing performance;

[0042] The mass ratio of the polypropylene, the polybutadiene nano rubber latex, the acrylamide and the lead oxide particles is 30:5:5:60.

[0043] Figure 1 This is a flow chart of preparing a polypropylene-based lead-shielding γ-ray composite material in Example 1; the figure shows the preparation process of the polypropylene-based lead composite material with excellent processing performance in Example 1.

[0044] Embodiment 2:

[0045] The difference between this embodiment and embodiment 1 is that the mass ratio of polypropylene, polybutadiene nano rubber emulsion, acrylamide and lead oxide particles is 60:5:5:30. The rest is the same as embodiment 1.

[0046] Embodiment 3:

[0047] The difference between this embodiment and embodiment 1 is that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is 50:5:5:40. The rest is the same as embodiment 1.

[0048] Embodiment 4:

[0049] The difference between this embodiment and embodiment 1 is that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is 40:5:5:50. The rest is the same as embodiment 1.

[0050] Embodiment 5:

[0051] The difference between this embodiment and embodiment 1 is that the mass ratio of polypropylene, polybutadiene nano rubber emulsion, acrylamide and lead oxide particles is 20:5:5:70. The rest is the same as embodiment 1.

[0052] Embodiment 6:

[0053] The difference between this embodiment and embodiment 1 is that the mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is 10:5:5:80. The rest is the same as embodiment 1.

[0054] Embodiment 7:

[0055] The present embodiment is different from the embodiment 1 in that no polybutadiene nano rubber emulsion and acrylamide are added, and the mass ratio of polypropylene to lead oxide particles is 60:40. The rest is the same as the embodiment 1.

[0056] Figure 2The complex viscosity-frequency curves of the polypropylene-based lead-shielding γ-ray composite materials prepared in Example 1, Example 3 and Example 7. It can be seen from the figure that the polypropylene-based lead composite materials prepared in Example 1 and Example 3 both have long-chain branching characteristics, and the shear thinning phenomenon of the composite material prepared in Example 1 is more obvious.

[0057] Figure 3 The melt flow rate (MFR) diagram of the polypropylene-based lead shielding γ-ray composite material prepared in Example 1 and Example 7. It can be seen from the figure that the polypropylene-based lead composite material prepared in Example 1 has a lower melt flow rate, a higher melt strength, and is easy to mold and process.

[0058] Figure 4 This is a scanning electron microscope image of the polypropylene-based lead shielding γ-ray composite material prepared in Example 1. It can be seen from the figure that the lead oxide particles in the polypropylene-based lead composite material prepared in Example 1 are uniformly dispersed in the polypropylene matrix, and have strong interface interactions with other particles.

[0059] Figure 5 The DSC curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Examples 1, 5 and 6 are shown. It can be seen from the figure that the lead oxide particles in the polypropylene-based lead composite materials prepared in Examples 1, 5 and 6 promote the crystallization and grain growth of the matrix polypropylene, and the lead oxide particles in the composite material prepared in Example 1 have a better effect on promoting the crystallization of the matrix polypropylene.

[0060] Figure 6 The XRD curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Example 1, Example 2 and Example 4 are shown in FIG. It can be seen from the figure that the polypropylene-based lead composite materials prepared in Example 1, Example 2 and Example 4 all have typical polypropylene α crystal form and β-PbO (orthorhombic system) characteristic peaks, and the β-PbO (orthorhombic system) characteristic peak of Example 1 is the strongest.

[0061] Figure 7 The thermogravimetric curves of the polypropylene-based lead shielding γ-ray composite materials prepared in Examples 1, 2 and 4 are shown. It can be seen from the figure that the carbon residue of the polypropylene-based lead composite materials prepared in Example 1 is higher than that in Examples 2 and 4, and the increase in the carbon residue is beneficial to improving the flame retardant properties of the composite materials. The carbon residue of the composite material in Example 1 is the largest.

[0062] Figure 8 The graph is an oxidation induction curve of the polypropylene-based lead shielding γ-ray composite material prepared in Example 1, Example 2 and Example 3. It can be seen from the figure that the lead oxide particles in the polypropylene-based lead composite material prepared in Example 1, Example 2 and Example 3 have an anti-thermal oxidation effect on polypropylene, and the oxidation induction time in the composite material of Example 1 is the longest, and the anti-thermal oxidation effect is better.

[0063] Fig. 9 The rheological time scanning curves of the polypropylene-based lead-shielding γ-ray composite materials prepared in Example 1 and Example 7 are shown. As can be seen from the figure, the storage modulus of the polypropylene-based lead-shielding composite material in Example 1 is significantly larger than that in Example 7, and the relaxation time is longer.

[0064] Fig.10 The following is a rheological temperature scanning curve of the polypropylene-based lead shielding γ-ray composite material prepared in Example 1 and Example 7. It can be seen from the figure that the storage modulus of Example 7 decreases faster in the higher temperature region than that of Example 1, and the composite material of Example 1 has better thermal stability.

[0065] Fig.11 The figure is a comparison of the linear attenuation coefficients of the polypropylene-based lead-shielded γ-ray composite materials prepared in Example 1 and Example 7. It can be seen from the figure that the probability of γ-rays being absorbed when passing through a unit distance in the composite material of Example 1 is greater, and the linear attenuation coefficient value is greater.

[0066] Fig.12 The figure is a comparison chart of the shielding efficiency of the polypropylene-based lead-shielding γ-ray composite materials prepared in Example 1 and Example 7. As can be seen from the figure, compared with the polypropylene-based lead-shielding composite materials prepared in Example 1 and Example 7, the composite material in Example 1 has a better shielding effect on γ-rays.

Claims

1. A method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance, characterized in that The method is specifically carried out in the following steps: Putting polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles into a torque rheometer, controlling the speed to be 30 rpm to 90 rpm and the temperature to be 160° C. to 220° C., melt blending for 5 min to 20 min, and then hot pressing on a flat vulcanizer to obtain the polypropylene-based lead shielding γ-ray composite material with excellent processing performance; The mass ratio of the polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (1-10): (1-10): (20-80).

2. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that Under the condition of controlling the rotation speed to be 40 rpm to 90 rpm, polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles are mixed for 5 min to 15 min.

3. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that The mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (2-10): (2-10): (20-80).

4. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that The mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65):(1-8):(1-8):(20-80).

5. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that The mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (5-65): (1-10): (1-10): (20-70).

6. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that The mass ratio of polypropylene, polybutadiene nano rubber latex, acrylamide and lead oxide particles is (10-55): (1-2): (1-2): (40-70).

7. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that The mixture is heated and stirred at a rotation speed of 30 rpm to 90 rpm and a temperature of 160° C. to 200° C. for 5 to 12 minutes.

8. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 7, characterized in that The mixture was heated and stirred at a rotation speed of 60 rpm and a temperature of 185° C. for 10 min.

9. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 1, characterized in that The hot pressing process controls the temperature to be 165-220° C. and the pressure to be 10-20 MPa.

10. The method for preparing a polypropylene-based lead shielding γ-ray composite material with excellent processing performance according to claim 9, characterized in that The hot pressing process controls the temperature to be 185-200° C. and the pressure to be 12-19 MPa.